Effect of Ocean Acidification on the Communications among Invertebrates Mediated by Plant-Produced Volatile Organic Compounds - Valerio Zupo; Mirko Mutalipassi; Patrick Fink; Marco Di Natale (Global Journal of Ecology - Peertechz Publications, 2016)
Chemical communications among plant and animal components are fundamental elements for the functioning and the connectivity of ecosystems. In particular, wound-activated infochemicals trigger specific reactions of invertebrates according to evolutionary constraints, permitting them to identify reycues, escape predators and optimize their behaviors according to specific life strategies. Thus, the orrect flux of information made possible by the production of plant infochemicals and its recognition by given invertebrates is fundamental to assure an appropriate functioning of complex ecosystems. However, global warming and ocean acidification (OA) are deeply influencing the metabolism of organisms and confounding their chemical communications. The production of plant secondary metabolites is influenced by global environmental changes and the OA can modify the effect of infochemicals, inducing dramatic modifications in the behavior of various animals. This research takes into account the effect of volatile organic compounds produced by epiphytes growing on a seagrass and the changes induced by OA in the chemotactic reactions exhibited by associated invertebrates. Our results demonstrate that behavioural influences may hamper the survival of key species of invertebrates, besides the direct effects of OA on their physiology.